2008
DOI: 10.1029/2008ja013121
|View full text |Cite
|
Sign up to set email alerts
|

Cluster observations of fast shocks in the magnetosheath launched as a tangential discontinuity with a pressure increase crossed the bow shock

Abstract: [1] The interaction of a tangential discontinuity (TD) and accompanying dynamic pressure increase with the Earth's bow shock launches a fast shock that travels ahead of the TD in the magnetosheath and carries a significant portion of the pressure change. In this event study, we use observations from the Cluster spacecraft and magnetohydrodynamic simulations to identify the fast shock and its properties and to track the TD in the magnetosheath. Velocities of the fast shock and the TD were determined by triangul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…Results from a three-dimensional magnetosheath numerical model show that both a fast reverse shock and a fast expansion wave (rarefaction wave) may result from the interaction of the IP shock with the magnetopause depending on boundary conditions of the model (Samsonov et al, 2006). The existence of the rarefaction wave reflected from the magnetopause due to the shock-magnetopause interaction was confirmed by a case study employing observations made by Cluster spacecraft in the magnetosheath (Maynard et al, 2008). Based on results from global MHD simulations, Samsonov et al (2007) suggested that the dayside ionosphere reflects the transmitted fast shock and that the bow shock and the magnetopause move sunward when the reflected fast shock passes.…”
Section: Introductionmentioning
confidence: 71%
“…Results from a three-dimensional magnetosheath numerical model show that both a fast reverse shock and a fast expansion wave (rarefaction wave) may result from the interaction of the IP shock with the magnetopause depending on boundary conditions of the model (Samsonov et al, 2006). The existence of the rarefaction wave reflected from the magnetopause due to the shock-magnetopause interaction was confirmed by a case study employing observations made by Cluster spacecraft in the magnetosheath (Maynard et al, 2008). Based on results from global MHD simulations, Samsonov et al (2007) suggested that the dayside ionosphere reflects the transmitted fast shock and that the bow shock and the magnetopause move sunward when the reflected fast shock passes.…”
Section: Introductionmentioning
confidence: 71%
“…In MHD the interaction of the bow shock and a TD containing a density increase enhances the compression of the plasma downstream of the bow shock and generates an additional fast shock that propagates Earthward ahead of the transmitted TD (e.g., Neubauer, ; Wu et al, ). Maynard et al () investigated such a case and identified the preceding fast shock in the magnetosheath using Cluster spacecraft data. In our case, the fast shock should be found earlier than the slow expansion fan.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of the bow shock with discontinuities has also been studied (e.g., Fairfield et al, ; Fairfield et al, ; Farrugia et al, ; Lin et al, ; Maynard et al, , ; Neubauer, ; Völk & Auer, ; Wu et al, ; Yan & Lee, ). Since the interaction can be well time correlated, the outcome of these interactions has been clearer than for fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the intense higher-frequency variations and a data gap, we were unable to identify unambiguously start times of the rarefaction wave at the locations of all four spacecraft as is needed to estimate its phase speed via triangulation. Fast waves mediate pressure changes and have been observed in the magnetosheath consequent to directional discontinuities with associated solar wind density changes impacting the bow shock [Maynard et al, 2007[Maynard et al, , 2008. No associated density change or dynamic pressure change is obvious in the ACE data associated with the ACE 4+ B Y reversal.…”
Section: Magnetosheath Consequences Of the Hps-hcs Magnetic Holementioning
confidence: 96%
“…As a result, the ion pressure tensor does not remain cylindrically symmetric about the magnetic field strength B, the E × B/B 2 is not equal to V ?i , and the MHD approximation is no longer valid. This is the third in a series addressing how directional discontinuities and associated pressure changes in the solar wind interact with the bow shock, magnetosheath, and magnetosphere [Maynard et al, 2007[Maynard et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%